If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 31 = -55 Reorder the terms: 31 + y = -55 Solving 31 + y = -55 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-31' to each side of the equation. 31 + -31 + y = -55 + -31 Combine like terms: 31 + -31 = 0 0 + y = -55 + -31 y = -55 + -31 Combine like terms: -55 + -31 = -86 y = -86 Simplifying y = -86
| 16-m^2=0 | | w^2+8w+48=0 | | 2[(3)+2]4= | | 0.4n-18=3n-16-0.9n | | a^2-10-3a= | | 6(2x-5)-3(x+2)-18x= | | 2(6-2b)=0 | | 2(3m-10)= | | 5y+2=3y-1 | | 2(3m+5)= | | 3x+6=89-5x | | -27=x+19 | | -2(5-3m)= | | 3(7)/3= | | 3z-(10)=1 | | log(12x^4)-log(2x^3)=2 | | 4(5+7b)+6b=-252 | | cos(x)=-0.5 | | 5ln(x-11)-3=7 | | 8x^2-6x-3=0 | | 3(5-15)=m-5 | | 3x+25=12x+83 | | 3a-1(-1)=-5 | | 4(3y-3)-2y=-9 | | 4v+-3v-4=13 | | 6x^2-2x^3-4x=0 | | 2k-16-10k=-2k | | 207-7x=38x+22 | | -12-3+9= | | 6(x+4)-(2x-8)= | | 5-(-8)=x | | y^2-5y-3=0 |